Counting Commission On Property Sale Transactions PT. Bumi Nusa Binangkit Using Microsoft Visual Basic version 6.0 - Desi Asmarani; Hj. Latifah Ssi, MMSI Hj. Latifah Ssi, MMSI (Jurnal Sistem Informasi, 2007)
These calculations aim to calculate the results of property sales and transactions print reports on the company's sales, with the use of science and engineering mathematics and to improve the ability to think logically and rationally effectiveness with the manager's decision. These calculations include property sales data obtained by each Marketing on every transaction later in the countdown based on the commission in a matter of per cent that will show the results of commissions in the can for Marketing.